Trauma-Informed Care and Health Among LGBTQ Intimate Partner Violence Survivors - Scheer, Jillian R. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) and its health consequences occur among lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals at rates equal to or higher than cisgender heterosexual individuals. Trauma-informed care (TIC) is one service approach with emerging empirical support for use with IPV survivors, but without attention to the LGBTQ population. Structural equation modeling was used to assess associations between TIC and mental and physical health through several mechanisms among 239 LGBTQ adults who had experienced IPV and sought healthcare services within the past year (Mage = 27.66; 66.7% White; 43.9% cisgender women). Participants reported their perceptions of TIC in their services received; their sense of empowerment, emotion regulation, shame, and social withdrawal (all conceived as mobilizing mechanisms through which TIC could be associated with health); and their mental health (depression and posttraumatic stress disorder [PTSD]), and physical health (somatic symptoms and chronic health conditions). Those who perceived greater TIC in their services reported greater empowerment and emotion regulation, and lower social withdrawal. In turn, lower social withdrawal and shame were associated with better mental health, while lower shame also was associated with better physical health. Indirect associations between TIC and mental and physical health through the four mobilizing mechanisms were not significant, however, with the exception of a small indirect effect on mental health through lower social withdrawal. Results suggest that practitioners need to develop services to be used in conjunction with a general TIC approach to improve health and target shame among LGBTQ IPV survivors.